Report on Improved Agricultural Implements in Madras State - (:unkn) unknown (Planning Commission, Government of India, 1963)
This consolidated report examines the development, dissemination, and institutional support for improved agricultural implements in Madras State, with comparative insights from Punjab and related discussions on agricultural engineering education and infrastructure. It identifies critical weaknesses in research coordination, manufacturing capacity, standardization, training, and distribution systems that have constrained the adoption of improved implements. Emphasis is placed on strengthening collaboration between agriculture and industry departments, upgrading artisan skills, establishing government-supported manufacturing and rural workshops, and improving extension-led demonstrations. The report also highlights the need for targeted credit facilities, systematic research and testing of implements, and reforms in agricultural engineering education and staffing. Collectively, the findings outline a comprehensive strategy to promote mechanization suited to local conditions, enhance productivity, and build a sustainable institutional framework for agricultural modernization.
Committee on Plan Projects (Agriculture Team) New Delhi October 1963
Keywords: Improved Agricultural Implements; Madras State Agriculture; Agricultural Engineering Research; Implement Standardization; Artisan Training Programs; Government Manufacturing Units; Rice-Based Cropping Systems; Extension Agency Demonstrations; Farm Mechanization Promotion; Rural Workshop Establishment; Agricultural Engineering Education Policy; Credit Facilities for Implements